2020
DOI: 10.1002/jcla.23428
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0023642 promotes proliferation, invasion, and migration of gastric cancer by sponging microRNA‐223

Abstract: Background Circular RNAs (circRNAs) have a closed‐loop structure and are associated with various cellular biological processes, including carcinogenesis and cancer development. However, our knowledge of circRNAs in gastric cancer (GC) remains limited. Thus, this study aimed to investigate the role and underlying molecular mechanisms of hsa_circ_0023642 in GC. Materials and methods Bioinformatic analysis revealed that hsa_circ_0023642 was upregulated in GC. Chromogenic in situ hybridization (CISH) chips was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Li et al 22 demonstrated the downregulation of hsa_circ_0001017 and hsa_circ_0061276 in GC tissues and plasma by RT‐droplet digital PCR (ddPCR). Zhang et al 23 reported that hsa_circ_0023642 was upregulated in GC and correlated with malignant progression of GC by acting as a miR‐223 sponge. Zhang et al 24 reported that circLARP4 can facilitate the expression of miR‐424‐5p target LATS1 and YAP by acting as a sponge of miR‐424‐5p.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al 22 demonstrated the downregulation of hsa_circ_0001017 and hsa_circ_0061276 in GC tissues and plasma by RT‐droplet digital PCR (ddPCR). Zhang et al 23 reported that hsa_circ_0023642 was upregulated in GC and correlated with malignant progression of GC by acting as a miR‐223 sponge. Zhang et al 24 reported that circLARP4 can facilitate the expression of miR‐424‐5p target LATS1 and YAP by acting as a sponge of miR‐424‐5p.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Similarly, circHN1, circMAN2B2, and hsa_circ_0023642 were also found to affect the growth and migration of GC cells by the similar ways. 16 , 17 , 18 All these circRNAs can serve as potential biomarkers and targets for the diagnosis and therapy of GC, which strongly suggests an important role of altered circRNAs in cancer pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“… 13 It was also revealed that circ_0023642 contributed to GC development via interaction with miRNA-223. 14 Ding et al reported that circCSNK1G1 was one of the markedly upregulated circRNAs in GC. 15 However, the biological role of circCSNK1G1 in GC is still unclear.…”
Section: Introductionmentioning
confidence: 99%